Factors the Reduction of Gombang Fishing Gear in Prapat Tunggal Village, Bengkalis Regency, Riau Province - Femi Riza; Roslimah Roslimah; Erliantina Ar-ridhaty Akita (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Prapat Tunggal Village was a central hub for gombang fishing gear because, on average, fishermen in this village used gombang fishing gear during their time. Gombang is a traditional fishing tool that was very popular among fishermen in the Bengkalis Strait, Bengkalis Regency. According to the report from the Fisheries and Marine Affairs Agency of Bengkalis Regency in 2013, it was recorded that there were 651 units of gombang fishing gear in operation. Then, there was an increase in 2016 by 71.6%, totaling 909 units. According to field surveys conducted by researchers since 2022, very few fishermen in Bengkalis Regency are now using gombang fishing gear and have switched to pengerih fishing gear. This research was conducted from July 6th to 10th, 2023, in Prapat Tunggal Village, Bengkalis Regency, Riau Province. The research object was the gombang fishing gear that was formerly commonly used by fishermen in Prapat Tunggal Village for fishing operations. The data obtained have been tabulated in the form of tables and graphs and analyzed statistically descriptively. The factors leading to fishermen switching from gombang to pengerih fishing gear include easier and safer fishing practices, as well as lower costs for purchasing and maintaining the gear. According to data from the Bengkalis Fisheries and Marine Affairs Agency in 2021, there were 413 units of gombang fishing gear in operation, while there were 1,282 units of pengerih fishing gear in operation.